Efektivitas Pengendalian Hama Penggerek Batang Padi Kuning (Scirpophaga incertulas) Menggunakan Perangkap Feromon Seks dengan Posisi dan Ketinggian yang Berbeda - Cahyaningrum, Estu; Tarmadja, Samsuri; Satya Santi, Idum (AGROISTA : Jurnal Agroteknologi, 2025)
This study evaluates the effectiveness of sex pheromone traps in controlling the Yellow Rice Stem Borer (Scirpophaga incertulas). Conducted from April to July in Kesesi Subdistrict, Central Java. The research employed a Randomized Block Design applied in the experiment with two factors: trap position (in-row and jajar legowo) and height (0.5 m, 1 m, 1.5 m), resulting in six treatment combinations across 18 experimental units. Data analysis was performed using ANOVA at a 5% significance level, followed by DMRT for significant results. The highest average capture of moths occurred at 31 days after planting in the treatment in Jajar Legowo position with a height of 0.5 meters with 17 heads. At 70 days after planting, the highest attack rate was 2.36%. Pheromone traps provide effective results in controlling Scirpophaga incertulas.